Structural and Chromatic Displacement in Contemporary Tunisian Painting: Pergeseran Struktural dan Kromatik dalam Lukisan Tunisia Kontemporer - Noumi, Dr. Bashar Jawad (Indonesian Journal of Education Methods Development, 2026)
General Background: Stylistics examines linguistic variation and expressive forms in literary and rhetorical discourse. Specific Background: Displacement is a central concept in Arabic stylistics, reflecting deviation from conventional language use to create aesthetic and semantic depth. Knowledge Gap: Despite extensive theoretical discussions, there is limited integration between classical Arabic rhetoric and modern stylistic analysis in examining displacement. Aims: This study aims to analyze the concept of stylistic displacement within Arabic discourse by exploring its linguistic, rhetorical, and critical dimensions. Results: The analysis shows that displacement operates as a key mechanism in shaping meaning through deviation, metaphor, and structural variation, supported by examples from classical and modern texts. It also reveals the continuity between traditional rhetorical concepts and contemporary stylistic frameworks. Novelty: The study bridges classical Arabic rhetorical theory with modern stylistic approaches, offering a comprehensive perspective on displacement. Implications: The findings contribute to a deeper understanding of linguistic creativity and provide a framework for analyzing literary texts within both traditional and modern critical contexts. Keywords: Stylistic Displacement, Arabic Stylistics, Rhetorical Analysis, Linguistic Deviation, Literary Criticism Key Findings Highlights Conceptual link established between classical rhetoric and modern analysis Deviation mechanisms shape semantic and aesthetic expression Analytical framework supports interpretation of literary texts